2002
DOI: 10.1159/000057783
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Silent Otitis media

Abstract: Otitis media occurs along a continuum. For example, otitis media with effusion characterized by fluid pathology can lead to chronic otitis media plus chronic mastoiditis, characterized by the presence of intractable tissue pathology such as cholesteatoma, cholesterol granuloma or granulation tissue. The literature defines chronic otitis media as having a tympanic membrane perforation and otorrhea. Amongst many other sequelae, which can result from the continuum, an important common one is chronic silent otitis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 27 publications
(29 reference statements)
0
20
0
Order By: Relevance
“…Yoon et al, 1990]. OM associated with few or no clinical symptoms or signs, and no or minimal effusion, has been detected in postmortem specimens [Meyerhoff et al, 1978;da Costa et al, 1992] (an entity termed 'chronic silent OM' [Paparella et al, 2002]). When a non-suppurative effusion is present, it varies quantitatively and qualitatively.…”
Section: Pathological Analysesmentioning
confidence: 99%
“…Yoon et al, 1990]. OM associated with few or no clinical symptoms or signs, and no or minimal effusion, has been detected in postmortem specimens [Meyerhoff et al, 1978;da Costa et al, 1992] (an entity termed 'chronic silent OM' [Paparella et al, 2002]). When a non-suppurative effusion is present, it varies quantitatively and qualitatively.…”
Section: Pathological Analysesmentioning
confidence: 99%
“…We found here that mucosal thickening less than 20 mm was rarely (5%) associated with an effusion, but thickening greater than 20 mm was almost always associated with an effusion (97%). Chronic otitis media without effusion has been described in the human population as so-called "silent otitis media" (Paparella et al, 2002), although the clinical significance of this entity is unclear. Regardless, we have shown here that if we disregard the presence or absence of middle ear effusion, oto-endoscopy is still a valid way of diagnosing mucoperiosteal thickening (inflammation).…”
Section: Endoscopic Assessment Reliability and Validitymentioning
confidence: 99%
“…The recent abuse of antimicrobial agents, however, has led to changes in the major pathogens causing CSOM and in their antibiotic sensitivities. Many studies have reported that the most frequently detected frequently in patients with CSOM are Staphylococcus and Pseudomonas aeruginosa (PA); increases in the resistance of these pathogens to antimicrobial agents have made them difficult to treat [4] . Empirical antibiotic treatment of patients with antibiotic-resistant bacteria, such as quinolone-resistant PA and methicillin-resistant Staphylococcus aureus (MRSA), which have been increasingly identified in infectious diseases, may result in treatment failure or complications [5,6] .…”
Section: Introductionmentioning
confidence: 99%